Fathers’ presence and adolescents’ interpersonal relationship quality: Moderated mediation model - Li, Ao; Sun, Li; Fan, ShiQing (Frontiers in Psychology, 2023)
Abstract This study examined the mechanism of fathers’ way of being present on father’s presence, adolescents’ social responsibility, and their quality of interpersonal relationships; if fathers adopt a democratic approach to be present, the study examines whether teenagers are more likely to enhance their sense of social responsibility and achieve harmonious interpersonal relationships. Participants were 1,942 senior high school and college students who responded to the Fatherhood Questionnaire, Social Responsibility Questionnaire, and Interpersonal Relationship Quality Diagnosis Scale. Results demonstrated that more harmonious interpersonal relationships were present among teenagers when fathers adopted a democratic upbringing, and this interaction effect on interpersonal relationships was mediated by teenagers’ sense of social responsibility. Our findings reveal the significance of emphasizing fathers’ democratic presence on teenagers’ sense of social responsibility and interpersonal relationships. The implications of the fathers’ efficient participation in family upbringing are discussed.